The bio-ecology of the blue tick (Boophilus decoloratus) in the central Free State - Phalatsi, Moeketsi Solomon (University of the Free State, 2002)
English: Boophilus decoloratus is the most dominant and economically important tick that infests cattle in the central Free State. Very little research on this tick in the central Free State has, however, been conducted. The broad objectives of this study were to investigate aspects of the oviposition and reproduction, tolerance of engorged females to sub-zero temperatures, and microhabitat selection, survival and seasonal abundance of non-parasitic larvae, and the seasonal dynamics of B. decoloratus parasitic on cattle in Botshabelo, central Free State. Engorged B. decoloratus females exposed to 10°C did not lay eggs whereas those kept at 15, 20, 25, and 30°C, respectively laid eggs. The shortest (3.5days) mean pre-oviposition period was recorded at 30°C and 75% RH and the longest (13.2 days) at 15°C and a RH of 35%. The developmental zero temperature for pre-oviposition was calculated at 9.138°e. The oviposition period was more extended at lower temperatures. The shortest mean oviposition period (8 days) was recorded at 30°C and 35% RH. Incubation was also more extended at lower temperatures. The developmental zero temperature for incubation was calculated at 4.73°C. This value was lower than expected and probably due to a smaller sample size or lack of values for eggs incubated between 10 and 15°C. Relative humidity did not affect the oviposition period or the pattern in daily egg production. Peak egg production (533) was reached within five days from the start of oviposition. B. decoloratus females lay average sized eggs. Females weighing more than 200mg produced an average of 11.4 eggs per mg of body mass. The average conversion efficiency index (Cêl) values recorded in this study recorded nutrient index (NI) values were 10-15% less than the recorded values for specific weight classes of B. microplus. Females exposed during May 1998 to naturally fluctuating conditions died during late winter (August) without laying eggs. Eggs which were laid during April and May did not accumulate sufficient temperature for eclosion to take place. Larval survival periods were inversely dependent on increased temperature accumulation. The results of this study have shown that engorged female ticks do not dig into the soil. The ticks seek refuge in cracks or openings in between gravel particles, or underneath debris. B. decoloratus is able to withstand exposure to sub-zero temperatures. Mortality, however, increased with an increase in exposure time. At an exposure temperature of -10°C and an exposure time of 8 hours, 40% of the females still managed to survive and lay eggs which hatched normally. The results further indicated that direct chilling injury could occur at <- 8°C, which may also be indicative of the supercooling point for engorged B. decoloratus. Investigations on the longevity of larvae under laboratory conditions have shown that temperature to a great extent affected survival as manifested by a relatively short survival period (2 days) of larvae kept at 30°C. In general the survival periods for the larvae were less than those reported in the literature. The differences are believed to be related to different methodologies that were used. The results of this study also indicated that B. decoloratus displayed an appetence behaviour by preparing an ambush for its hosts. The larvae migrated vertically and showed a preference for longer (45cm) compared to shorter (5 and 25cm) questing substrates. The larvae formed clusters at the tips of the questing substrates. B. decoloratus ticks were present on cattle all year round. The numbers were, however, low during July to September. Peak adult numbers were collected from cattle during April and May, respectively. Nymphs and larvae displayed peaks during February and April, respectively. It was surmised that B. decoloratus can complete three generations per year in the central Free State. The overall sex ratio of the ticks collected from cattle did not differ from unity. This did not conform to the general pattern of male dominance observed for other metastriate ticks. B. decoloratus was the most abundant larvae collected from the drags. The off and on host seasonal abundance of B. decoloratus larvae correlated well. Drag sampling provided a fairly accurate indication of, not only the seasonal abundance of questing larvae, but also the species conditiosition in the Botshabelo area.

Afrikaans: Boophilus decoloratus is die mees dominante en ekonomies belangrike bosluis wat beeste in die sentrale Vrystaat besmet. Min navorsing is egter in die verlede op hierdie bosluis in die Vrystaat uitgevoer. Die breë doelstellings van hierdie studie was om aspekte van eierlegging en reproduksie tolleransie van volgesuigde wyfies teen sub-zero temprature en mikrohabitat seleksie, oorlewing en seisoenale voorkoms van nie-parasitiese larwes, en die seisoenale dinamika van B.decoloratus parasities op beeste in Botshabelo te ondersoek. Volgesuigde B.decoloratus wyfies wat aan l O'C blootgestel was het nie eiers gelê nie, terwyl die wat by 15, 20, 25 en 30°C gehou is, wel eiers gelê het. Die kortste (3.5 dae) gemiddelde voor eierleggings tydperk is by 30°C en 75% RH aangeteken, terwyl die langste (13.2dae) by 15°C en 35% RH aangeteken is. Die ontwikkelings zero temperatuur vir voor eierlegging was 9.138°e. Eierlegging het langer geduur by laer temprature. Die kortste (8dae) gemiddelde eierleggingsperiode was by 30°C en 'n 35% RH aangeteken. Inkubasie het ook oor'n meer verlengde tydperk plaasgevind by laer temprature. Die ontwikkelings zero temperatuur vir inkubasie was 4.73°C. Hierdie waarde is laer as wat verwag is en is waarskynlik te wyte aan 'n klein monstergrootte of 'n tekort aan waardes vir eiers wat tussen 10 en 15°C geinkubeer is. Relatiewe humiditeit het nie eierlegging of die daaglikse patroon in die lê van eiers beinvloed nie. Piek eierproduksie (533) is binne vyf dae vanaf die aanvang van eierlegging bereik. B. decoloratus wyfies lê eiers van 'n gemiddelde grootte. Wyfies wat meer as 200mg weeg produseer gemiddeld 11.4 eiers per mg liggaamsmassa. Die gemiddelde omskakelings doeltrefIenheids indeks (CEQ waardes tydens hierdie studie is as 49.36% bereken, wat naby die waardes is wat vir ander Boophilus species bereken is. Die voedings indeks (Nl) waardes wat tydens hierdie studie bereken is was 10-15% minder as die waardes wat vir B. microplus bereken is. Wyfies wat tydens Mei 1998 aan natuurlike flukterende toestande blootgestel is, het tydens die laat winter (Augustus) gevrek sonder om eiers te lê. Eiers wat tydens April en Mei gelê is het nie genoeg hitte geakkumuleer vir ontwikkeling om plaas te vind nie. Die oorlewing van larwes was omgekeerd afhanklik van 'n toename in tempratuur akkumulasie. Die resultate van hierdie studie het aangetoon dat wyfies nie in die grond ingrawe nie. Die bosluise soek skuiling in krake in die grond of in openinge tussen gruiskorrels, of onder debrie. B. decoloratus kan blootstelling aan sub-zero temprature oorleef Mortaliteit neem egter toe met 'n toename in die blootstellings tydperk. By 'n blootstellings temperatuur van - 10°C en 'n blootstellings tyd van 8 ure, het 40% van die wyfies daarin geslaag om te oorleef en eiers te lê wat normaal uitgebroei het. Die resultate het verder aangedui dat direkte ysingwekkende skade by <-8°C kan voorkom, wat ook moontlike 'n aanduiding van die superverkoelingspunt van volgesuigde B. decoloratus is. Ondersoek na die langlewendheid van larwes onder laboratoruim toestande het aangedui dat temperature in 'n baie groot mate die lewensduurte bepaal. So byvoorbeeld het larwes slegs vir twee dae by 30°C oorleef. Oor die algemeen was die oorlewingstydperk wat vir larwes aangeteken is korter as die waardes wat in die literatuur aangehaal word. Die verskille is waarskynlik te wyte aan verskillende metodes wat gevolg is. Die resultate van hierdie studie het ook aangedui dat larwes na gashere soek deur vertikaal te migreer op substrate en 'n lokval te stel. Die larwes het egter 'n voorkeur getoon om op langer (45cm) vergeleke met korter (5 en 25cm) substrate vertikaal te migreer. Die larwes het in bondels naby die punte van die metaaldrade voorgekom. B. decoloratus het heeljaar op beeste voorgekom. Die getalle was egter laag tydens Julie en September. Piek volwassene getalle het tydens April en Mei op die beeste voorgekom. Nimfe en larwes het pieke in voorkoms tydens Februarie en April getoon. Die resultate dui daarop dat B. decoloratus moontlik drie generasies per jaar in die sentrale Vrystaat kan voltooi. Die geslagsverhouding van die bloubosluise wat op die beeste voorgekom het, het nie van mekaar verskil nie. Dit is teenstrydig met waarnemings op ander metastriaat bosluise waar mannetjies gewoonlik oorheersend in getalle is. B. decoloratus is die mees volopste bosluis larwes wat tydens slepe versamel is. Die slepe het 'n redelike akkurate aanduiding gegee van die samestelling en seisonale voorkoms van larwes wat op die grasse voorgekom het.
Keywords: Boophilus decoloratus; Pre-oviposition period; Oviposition period; Incubation period; Conversion efficiency index; Nutrient index; Engorgement mass; Larval survival period; Seasonal dynamics; Vertical migration; Ticks; Ticks as carriers of disease -- South Africa -- Free State; Cattle -- Parasites; Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2002